Can online higher education be an active agent for change? —comparison of academic success and job-readiness before and during COVID-19 - Alam, Gazi Mahabubul; Parvin, Morsheda (Elsevier, 2021)
Adherents claim that online education mediated through technology can change society for the better, but critics assert that it has failed to produce job- or career-ready graduates. With this in mind, the present study examines the performance of academic and job-readiness of two groups of graduates. One group comprised a pre-COVID-19 cohort for face-to-face teaching mode while the other used the online mode during the pandemic. While the official secondary data are collected from the sampled university, primary data are gathered through an ‘empirical survey’ of 120 students in each group (i.e., before and during COVID-19, a total of 240). Findings suggest that the pre-pandemic group did poorly academically unlike their during-pandemic counterparts. Although both groups achieved well academically, there is a difference when comparing their job-readiness scores which included both aptitude and practicum tests. The pre-COVID-19 students achieved better job-readiness scores than their counterparts. Performance in academy and job-readiness is not proportionately linked. These findings suggest that higher education is generally not that active from the job market perspective, while online learning has in fact made education much more passive. Under any circumstances, the integrity of HE should not be compromised and hence a policy framework is hereby suggested to ensure that it functions well during an emergency period.